1987
DOI: 10.2307/1939859
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Host‐Plant Fertilization on an Insect Community

Abstract: Artemisia ludoviciana plants that received ammonium nitrate fertilizer were visually censused for all insects at ° 11 -d intervals from 30 June to 1 September 1982. Community composition and species densities in fertilized plots were compared with those in control plots. Fertilization resulted in greater numbers of phloem- and seed-feeding insects and a concurrent increase in tending and patrolling by ants in fertilized plots. Chewing-insect densities did not respond uniformly to fertilization, and no chewing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 25 publications
4
40
1
Order By: Relevance
“…However, the estimates of species richness from individual-based rarefaction did not increase with fertilization for any trophic group. Numerous studies have examined the diversity of herbivorous or other arthropods in response to fertilization, but generalizations have been elusive (e.g., Hurd and Wolf 1974;Kirchner 1977;Kajak 1981;Vince et al 1981;Prestidge 1982;Strauss 1987;Sedlacek et al 1988;Siemann 1998;Haddad et al 2000). However, several of these studies observed higher abundance of sap-sucking Auchenorryncha and other herbivorous groups, but decreasing evenness and diversity as a small number of species emerged as dominant (Prestidge 1982;Sedlacek et al 1988;Haddad et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, the estimates of species richness from individual-based rarefaction did not increase with fertilization for any trophic group. Numerous studies have examined the diversity of herbivorous or other arthropods in response to fertilization, but generalizations have been elusive (e.g., Hurd and Wolf 1974;Kirchner 1977;Kajak 1981;Vince et al 1981;Prestidge 1982;Strauss 1987;Sedlacek et al 1988;Siemann 1998;Haddad et al 2000). However, several of these studies observed higher abundance of sap-sucking Auchenorryncha and other herbivorous groups, but decreasing evenness and diversity as a small number of species emerged as dominant (Prestidge 1982;Sedlacek et al 1988;Haddad et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other agrochemicals, such as fertilizer, may indirectly increase ant predatory activities. For example, with synthetic fertilizers, populations of hemipteran pests like aphids and scale insects may increase, resulting in increased activity of hemipteran-tending ants, many of which are also predatory (Strauss, 1987). Certain agrochemicals may vary in their effects on ants and predatory activity (Andersen et al, 2002), but because we combined effects of all agrochemicals on into one index, the individual, slightly nuanced effects of different chemicals used may have been thus masked.…”
Section: Season Habitat and Vegetation And Agrochemical Indicesmentioning
confidence: 99%
“…Ant-hemipteran mutualisms, in particular, structure tropical arboreal communities (Floren et al 2002, Davidson et al 2003) and can be mediated by the indirect effects of nutrient availability on host-plant quality (Baylis andPierce 1991, Cushman 1991). Ant abundance increases on plants with high nutrient availability or with high plant quality due to increases in honeydew-producing herbivore abundance (Strauss 1987) or subsequent increases in the quality of honeydew rewards.…”
Section: Introductionmentioning
confidence: 99%